Lipschütz Ulcer, a Stressor and Inconvenient Situation of Vulvar Ulcer in Sexual Inactive Girls: Enhancment of Healing Process through Surgery - Giovani, Maria G.; Gentimi, Fotini; Karetsos, Chris; Baltogiannis, Nikolaos; Mavridis, Georgios (Medicine and Medical Research: New Perspectives Vol. 5, 2024)
The case of a 12-year-old girl with a single painful genital ulcer lesion in the context of CMV infection is presented, primary cause and the management of the disease are discussed. Lipschutz ulcers (LU) are presented as a highly inconvenient situation that an unsullied girl may suffer. They are painful lesions on the genital mucosa of females accompanied by fever and lymphadenopathy. The primary cause of the disease remains unknown. Causative factors that have been proposed to be associated with the disease include infections due to viruses or bacteria. Such as Epstein-Barr (EBV), Herpes Simplex Virus (HSV), Cytomegalovirus (CMV) and influenza type A viruses, adenoviruses, Salmonella SARS-COV-2 or vaccination. The case of a 12-year-old female with a genital single Lipschutz ulcer in the context of CMV infection is presented. The ulcer was made more complicated by cellulitis and rapid necrosis. Finally, the ulcer was replaced by an eschar on the 4th day of hospitalization. This includes a discussion of the differential diagnosis, the therapy, and the primary clinical symptoms. The current investigation used PCR to confirm the connection between Lipschutz ulcer and systemic Cytomegalovirus infection. Using symptomatic treatment (antimicrobial, antiviral) did not improve the ulcer's healing process; but, following surgical intervention, the ulcer healed considerably better. Follow-up management did not reveal a relapse. Further studies are needed to investigate the precipitating factors for the presence of LU. Surgical consultation should be immediately considered when symptoms of relapse appear. The surgical intervention combined with the administration of antibiotics also annihilates the risk of superinfection and complications of vulvar cellulitis.